2000
DOI: 10.1192/apt.6.4.252
|View full text |Cite
|
Sign up to set email alerts
|

Management of schizophrenia in conditions of high security

Abstract: There are four high-security hospitals in the UK: Broadmoor Hospital in Berkshire (founded in 1863), Rampton Hospital in Nottinghamshire (1914), Ashworth Hospital in Merseyside (1990), which opened following the amalgamation of Park Lane (1974) and Mosside Hospitals (1913), and the State Hospital at Carstairs in Lanarkshire (1948). The first three are known as the special hospitals and serve England and Wales. The latter offers a special security service, combining high and medium secure care, for the whole of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 30 publications
0
4
0
1
Order By: Relevance
“…In addition, the Centre admits Saskatchewan provincial inmates in need of psychiatric services in a maximum-security environment, individuals admitted for pre-trial psychiatric assessment and those found not to be criminally responsible on account of mental disorders. The RPC qualifies as a high-level secure hospital according to Thomson's criteria [27]. The medical records of all those who died during the study period were identified and perused in order to complete the information sheet developed specifically for this study.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the Centre admits Saskatchewan provincial inmates in need of psychiatric services in a maximum-security environment, individuals admitted for pre-trial psychiatric assessment and those found not to be criminally responsible on account of mental disorders. The RPC qualifies as a high-level secure hospital according to Thomson's criteria [27]. The medical records of all those who died during the study period were identified and perused in order to complete the information sheet developed specifically for this study.…”
Section: Methodsmentioning
confidence: 99%
“…Hal ini sangat penting pada pengamatan jalannya perbaikan/kemajuan program social skill secara umum dan dalam jangka waktu yang lama, serta keuntungan yang diperoleh dalam lingkungan masyarakat tersebut. 3, 5,7 Pelaksanaan social skill training dapat dilakukan antara lain dengan: 7,13…”
Section: Pelaksanaan Social Skill Trainingunclassified
“…The shift of focus from risk prediction to risk prevention emphasizes the need for care to be proactive rather than reactive. 27 In practice, this means that all risk management information, such as treatment planning, formulation and review documents, needs to be transparently clear to all staff involved in the treatment of patients. 28 At the State Hospital, risk assessment and management were completed and discussed by the multidisciplinary teams within a care and treatment planning approach thereby allowing the team to provide realistic and collaborative care.…”
Section: Description Of the Setting And Context Of The Implementationmentioning
confidence: 99%